PENERAPAN PEMBELAJARAN DENGAN PRAKTIKUM PEMBUATAN KOMPOS TERHADAP KARAKTER DAN HASIL BELAJAR SISWA - Ardianto, Alexander Danang; Priyono, Bambang (Journal of Biology Education, 2014)
Abstract _________________________________________________________________ The aim of this study is to analyze application learning with compost processing practical in environmental management subject to increase environmental careness characters and learning outcomes of seventh grade student in Junior High School 1 Ungaran.This study is a Pre Experimental Design. The study design uses the one group pretest-posttest design. The population in this study is every seventh grade students of Junior High School 1 Ungaran. The sample is students of class VII D and VII H.The results show that after learning 90% students have achieved very good and good criteria or increase 34% than before (56%). Learning outcomes of all students is completed with classical completeness 100%. t value in the t test is 8.597 in  VII D and 8.054 in VII H whereas for the t table is 1.69. This result show that t count > t table so learning effect to learning outcome. The analysis shows 94.44% of students in class VII D and 86.11% of students in class VII H give very good response about the learning. All science teachers in the both class give a positive response,  that the learning has been running very well. Based on the results of research and discussion, it can be concluded that the application of learning with composting processing practical affect in increasing the environmental careness characters and student learning outcomes in environmental management subject.  Abstrak___________________________________________________________________Penelitian ini bertujuan untuk menganalisis penerapan pembelajaran dengan praktikum pembuatan kompos dalam meningkatkan karakter peduli lingkungan dan hasil belajar siswa. Penelitian ini merupakan penelitian Pre Experimental Design. Rancangan penelitian menggunakan pola one group pretest-posttest design. Populasi dalam penelitian ini adalah seluruh siswa kelas VII SMP Negeri 1 Ungaran, sedangkan sampelnya adalah siswa kelas VII D dan VII H. Hasil penelitian menunjukkan bahwa 90% siswa memiliki karakter peduli lingkungan pada kriteria sangat baik dan baik atau naik 34% dari sebelumnya 56%. Hasil belajar semua siswa tuntas dengan ketuntasan klasikal 100%. Hasil uji t dari nilai pretest dan nilai posttest, didapatkan t hitung pada kelas VII D adalah 8,597 dan di kelas VII H adalah 8,054 sedangkan untuk t tabel adalah 1,69. Maka t hitung > t tabel maka ada pengaruh dari pembelajaran. Tanggapan siswa menunjukkan 94,44% siswa di Kelas VII D dan 86,11% di kelas VII H menyatakan pembelajaran sangat baik.   Semua guru IPA di kedua kelas memberi tanggapan positif dan menyatakan bahwa pembelajaran sangat baik. Berdasarkan hasil penelitian dan pembahasan disimpulkan bahwa pembelajaran dengan praktikum pembuatan kompos berpengaruh terhadap peningkatan karakter peduli lingkungan dan hasil belajar siswa kelas VII SMP Negeri 1 Ungaran.